Signal-Cooperative Multilayer-Modulated VLC Systems for Automotive Applications - Yan-Yu Zhang; Hong-Yi Yu; Jian-Kang Zhang; Yi-Jun Zhu (IEEE Photonics Journal)
In visible light communication (VLC) systems for automotive applications, different kinds of traffic data with intended priority are usually demanded for transmission to meet an important requirement for both driving safety and the simplicity of a receiver, mainly due to a time urgency issue. For this need, a concept called an additively uniquely decomposable constellation (signal amplitude set) group (AUDCG) is proposed in this paper to transmit multilayer data for VLC through constellation cooperation. Then, an optimal AUDCG is designed by minimizing the average optical power subject to a fixed minimum Euclidean distance. One of the significant advantages of this optimal design is fast demodulation of the sum signal from a noisy received signal, as well as fast decoding of individual signal from the estimated sum signal. Another important advantage is that this design allows each user constellation to be flexibly assigned to meet different priority requirements. Computer simulations indicate that our proposed design has better error performance than the currently available time-orthogonal transmission scheme for this application.